Global characterization factors for quantifying the impacts of increasing water temperature on freshwater fish. (September 2022) - Li, Dan; Dorber, Martin; Barbarossa, Valerio; Verones, Francesca
Graphical abstract: Highlights: Global characterization factors for impacts of water temperatures on freshwater fish. Characterization factors for 207 greenhouse gases and four future climate scenarios. Developed six species distribution for two thermal effects and three climate regions. Two applications for both regional impacts and global impacts. Abstract: Water temperature is an abiotic master variable for the survival of aquatic organisms. Global warming alters the thermal regimes of rivers and, thus, poses a threat to freshwater biodiversity. To address the impacts of water temperature changes related to global warming on freshwater fish species in life cycle assessment (LCA), we developed spatially explicit characterization factors (CFs) for 207 greenhouse gases under four representative concentration pathways. We calculated fate factors by using the output of a global hydrological model fully coupled with a dynamic water temperature model. We developed six species sensitivity distribution curves for two thermal effects (i.e., lethal and sub-lethal) to derive effect factors, which take the differences in sensitivity between climate regions into account. The regional CFs for CO2 ranged from 2.91 × 10 −22 to 6.53 × 10 −18 PAF·yr/kg for sub-lethal effects and from 1.98 × 10 −22 to 4.58 × 10 −18 PDF·yr/kg for lethal effects, depending on the river watersheds and future climate scenarios. To identify the contribution of regional impacts on freshwater fish to their potential global extinction, the regional CFs were converted into global CFs. The largest CFs always occur in the tropical watersheds. The regional impacts in the Amazon watershed contribute the most to the global freshwater fish species extinction. This study contributes to assessing the potential impacts on freshwater biodiversity from global warming from a new cause-effect pathway in LCA.